Power relations between managers and politicians: The resign of managers in conjunction with university hospital mergers - Nordgren, Lars (Scandinavian Journal of Public Administration, 2015)
The purpose of this article was to analyse how power relations drive hospital managers to resign in conjunction with three university hospital mergers in Sweden. Interviews were carried out with leading politicians and managers during two studies of mergers. In a third study, a paraphrased text from a previous study was used. Discourse analysis of the interviews revealed power struggles between politicians and managers, leading to situations of distrust. As the merger processes were additionally perceived to entail negative consequences for the patients and staff in the mass media the managers’ positions were undermined and they were in all the cases forced to resign by politicians. By using the notions of power relations and subjectification this power mechanism worked was analysed. Three themes emerged from the analysis; collision between values, displacement of responsibility and the resign of the manager. When leading politicians built alliances with leading professions in criticizing the hospital manager publicly, the manager lost trust.